Efficacy of the Herpes Simplex Virus 2 (HSV-2) Glycoprotein D/AS04 Vaccine against Genital HSV-2 and HSV-1 Infection and Disease in the Cotton Rat Sigmodon hispidus Model - Boukhvalova, Marina (J Virol, 2015)
Subunit vaccines based on the herpes simplex virus 2 (HSV-2) glycoprotein D (gD-2) have been the major focus of HSV-2 vaccine development for the past 2 decades. Based on the promising data generated in the guinea pig model, a formulation containing truncated gD-2, aluminum salt, and MPL (gD/AS04) advanced to clinical trials. The results of these trials, however, were unexpected, as the vaccine protected against HSV-1 infection but not against HSV-2. To address this discrepancy, we developed a Depot medroxyprogesterone acetate (DMPA)-treated cotton rat Sigmodon hispidus model of HSV-2 and HSV-1 genital infection. The severity of HSV-1 genital herpes was less than that of HSV-2 genital herpes in cotton rats, and yet the model allowed for comparative evaluation of gD/AS04 immunogenicity and efficacy. Cotton rats were intramuscularly vaccinated using a prime boost strategy with gD/AS04 (Simplirix vaccine) or control vaccine formulation (hepatitis B vaccine FENDrix) and subsequently challenged intravaginally with HSV-2 or HSV-1. The gD/AS04 vaccine was immunogenic in cotton rats and induced serum IgG directed against gD-2 and serum HSV-2 neutralizing antibodies but failed to efficiently protect against HSV-2 disease or to decrease the HSV-2 viral load. However, gD/AS04 significantly reduced vaginal titers of HSV-1 and better protected animals against HSV-1 compared to HSV-2 genital disease. The latter finding is generally consistent with the clinical outcome of the Herpevac trial of Simplirix. Passive transfer of serum from gD/AS04-immunized cotton rats conferred stronger protection against HSV-1 genital disease. These findings suggest the need for alternative vaccine strategies and the identification of new correlates of protection. IMPORTANCE In spite of the high health burden of genital herpes, there is still no effective intervention against the disease. The significant gap in knowledge on genital herpes pathogenesis has been further highlighted by the recent failure of GSK HSV-2 vaccine Simplirix (gD/AS04) to protect humans against HSV-2 and the surprising finding that the vaccine protected against HSV-1 genital herpes instead. In this study, we report that gD/AS04 has higher efficacy against HSV-1 compared to HSV-2 genital herpes in the novel DMPA-synchronized cotton rat model of HSV-1 and HSV-2 infection. The findings help explain the results of the Simplirix trial.